Strategi Pemasaran terhadap Produksi Abon Ikan Lele Berbasis Syariah di Daerah Padon Sendangrejo - Rohmansyah; Syarif As’ad (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Padon is a strategic village used as a place for catfish business and rice farming and animal husbandry. So that Padon is strategic enough to develop the community's economy, in addition to its abundant water, beautiful natural conditions that support making handicrafts and businesses of catfish, shredded catfish and others. Some of them have collaborated with entrepreneurs, but in the business of making shredded catfish, they still experience difficulties in marketing or sales problems because they do not know much about marketing strategies. This service aims to improve the economy of small and medium enterprises, especially the marketing of Abon Catfish. The implementation method used is observation, interviews, marketing training. The results of service as part of what is offered in a sharia-based marketing strategy are making good catfish floss packaging, making quality catfish shredded production, making a more varied list of catfish shredded menus, making social media such as facebook, instagram, telegram and youtube and other media. In addition, doing sharia-based marketing to avoid the element of fraud.